Dysphagia bedside evaluatation in adults with nasogastric tube - Grigaliūnaitė, Saulė; Kantanavičiūtė-Petružė, Rita (Slauga. Mokslas ir praktika, 2021)
The theoretical analysis of scientific literature sources and practice show that standardized adult assessment tools for the evaluation of adult swallowing disorders and readiness for withdrawal of the nasogastric tube (NGZ) are not uniformly used in Lithuanian health care institutions. The theoretical analysis of the assessment of swallowing disorders in adults fed by NGZ in the article showed that in the early stage of the disorder, examinations that are performed in the patient's ward and do not require radiological evaluation are sufficiently accurate. The aim of the study is to reveal the tools and methodologies for the evaluation of swallowing disorders in adults fed by NGZ in the patient's ward during the acute period of the disease. After the theoretical analysis of scientific literature sources, it can be stated that: enteral feeding improves feeding quality, but it restricts patient's movements, complicates communication, induces isolation; accurate assessment of dysphagia can be made by performing a swallowing sample in the patient’s ward; assessment of swallowing function takes into account masticatory muscle function, movements of lips, tongue and soft palate, swallowing, cough and gag reflex, oral control, oral residue, voice quality after swallowing and aspiration risk.
Keywords: oropharyngeal dysphagia; nasogastric tube feeding; swallowing disorders